Evaluation Of the Sedimentation Process in the Thickener by Using the Parameters of Longitudinal Ultrasonic Oscillations and Lamb Waves - MORKUN, Vladimir; MORKUN, Natalia; TRON, Vitalii; SERDIUK, Oleksandra; HAPONENKO, Alona (Archives of Acoustics, 2023)
Water is widely used in the mining industry, particularly in mineral enrichment processes. In the process of magnetic separation or flotation of crushed ore, a concentrate (an enriched product), and tailings (a product with a low content of a useful component) are obtained. One of the main tasks of enrichment processes is the efficient use of water resources. This is achieved by reclaiming and subsequent reusing water contained in ore beneficiation products by extracting it in industrial thickeners. Optimizing this process makes it possible to reduce water usage in the mining industry, reduce costs of mineral enrichment processes, and address extremely urgent environmental protection problems. To evaluate the process of sedimentation of the solid phase in the pulp within the thickener, measurements of parameters of longitudinal ultrasonic oscillations and Lamb waves that have traveled a fixed distance in the pulp and along the measuring surface in contact with it are used. The proposed approach allows for the consideration of pulp density, particle size of the solid phase in the ore material and the dynamics of changes in these parameters in the thickener at the initial stage of the sedimentation process. Based on the obtained values, adjustments can be made to the characteristics of its initial product, leading to reduced water usage and minimized loss of a useful component.